The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/01635581.2015.1004735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zinc Sulfate Supplementation on Cell-Mediated Immune Response in Head and Neck Cancer Patients Treated with Radiation Therapy

Abstract: Zinc deficiency is an important factor that impairs cellular immunity and contributes to low T lymphocyte counts in head and neck cancers. Persistent T lymphopenia is clinically relevant in terms of tumor persistence and/or recurrence. The primary objective was to evaluate the impact of zinc sulfate supplementation on the absolute numbers of circulating T lymphocytes and T lymphocyte subpopulations. The secondary objectives were to evaluate overall survival, progression-free survival, and the adverse events of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The incidence of xerostomia and pain decreased in zinc supplementation group more than in the placebo group in one of the studies (7,17). However, the quality of life did not undergo a significant change to that of the controls with the usage of zinc.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The incidence of xerostomia and pain decreased in zinc supplementation group more than in the placebo group in one of the studies (7,17). However, the quality of life did not undergo a significant change to that of the controls with the usage of zinc.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, a study by Sangthawan et al showed that the zinc had no effect on the number or the survival of circulating T lymphocytes (17). Areca nut chewing with increased copper content may have had a significant role when such lesions were treated with zinc therapy, because of potential interaction of zinc with mucosal metaallothionein, interfering with copper metabolism (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, its antitumoral effect seems to be mediated by anti-inflammatory, antioxidant, and immunostimulatory actions [62] (Figure 1). Furthermore, in head and neck cancers, a zinc deficit mediates cellular immunity impairment, contributing to a decrease in T lymphocyte numbers and such effect can be reverted by zinc sulfate supplementation [63].…”
Section: Other Components Of Oosmentioning
confidence: 99%
“…19,20,60 Interestingly, Zn deficiency has been reported in a large percentage of patients with head and neck, breast, and gastrointestinal (GI) system cancers. [60][61][62] Some studies have investigated the chemopreventive effects of Zn on several cancers such as gut, liver, and lung cancer. 31,63,64 In addition, it has been found that supplementation with combinations of retinol and Zn does not decrease primary liver and lung cancer mortality.…”
Section: The Role Of Zn In Cancermentioning
confidence: 99%